Shared poverty as a myth: Agricultural communities in Bojonegoro, East Java, 1880s–1930s - Akhyat, Arif (Balai Pelestarian Kebudayaan Wilayah X, 2024)
This article explains the endemicity of poverty in Bojonegoro 1880-1930s by analyzing the causes and social-economic changes among agrarian communities. Bojonegoro is one of the regions in East Java that is experiencing a paradoxical process, one side has a strategic location for economic networks, but the other side is an endemic area for natural disasters. As a study of social history, poverty in this article focuses more on dysfunctional social institutions due to geographical location, natural disasters, and the marginalization process as a form of the state's absence from the problem of poverty. Historians often conclude that disasters and geographical issues are necessary conditions in explaining the endemicity of poverty. This study shows that poverty is only an easy way to explain the inability to adapt to local economic dynamics and failure to negotiate with the new market. The infrastructure development and financial institutions which are considered to be strategies for overcoming poverty, does not have clear significance. Poverty does not refer to socio-economic realities with various survival strategies using socio-economic networks and job conversion. The strategy of adapting to various economic opportunities, both based on agrarian and non-agrarian economies, is a way to show that the endemicity of poverty is a myth. The poverty is a form of failure to explain socio-economic behavior which is considered to deviate from the view of modern capitalism.